Karakterisasi Sediaan Granul Biji Sirsak (Annona muricata L.) dan Uji Efektivitas terhadap Larva Aedes aegypti L. sebagai Kandidat Biolarvasida - SARAH ZAIDAN; RATNA DJAMIL; SUPRIYONO SUPRIYONO; SITI Nuraini (Fakultas Farmasi Universitas Pancasila, 2016)
A. aegypti mosquito is a vector of virus caused dengue fever. The effort to control A. aegypti vector has been done so many times, including chemical, physical and biological method. A biological control against this vector can be performed by utilizing soursop seeds which are known to have larvicidal effect against the larva. Previously, it has been proven that the extract of soursop seed demonstrated larvicidal activity against A. aegypti. In this research, the extraction of soursop seed has been carried out by kinetic maceration with the solvent 70% of ethanol. Furthermore, the wet granulation of the obtained extract was used for the preparation of granules which were then tested its larvicidal activity against A. aegypti. Based on the activity test against the larva of Aedes aegypti, the granules showed LC50 values of 295.434 ppm smaller than temephos as a positive control that has larvicidal activity of 1 ppm cause 100% mortality A. aegypti.